Alien encounters : (Duke University Press, 2007)
Alien Encounters showcases innovative directions in Asian American cultural studies. In essays exploring topics ranging from pulp fiction to multimedia art to import-car subcultures, contributors analyze Asian Americans’ interactions with popular culture as both creators and consumers. Written by a new generation of cultural critics, these essays reflect post-1965 Asian America; the contributors pay nuanced attention to issues of gender, sexuality, transnationality, and citizenship, and they unabashedly take pleasure in pop culture.